Co-benefits (improved productivity, profitability and environmental friendliness ) of site-specific nutrient management for maize, rice, and wheat tailored to smallholder agriculture - CGIAR Research Program on Rice (2021)
Relative to the farmer practice, across the crops maize, rice and wheat, Site Specific Nutrient Management (SSNM) increased grain yield by 12% and profitability by 15% with 10% less fertilizer nitrogen applied, thereby improving nitrogen use efficiency and reducing nitrogen pollution to the environment.